Aluminum Exchangeable and Phosphorous Availability on Ultisol Using Humic Substance and Synthetic Organic Acid - Sugeng Winarso; Abdullah Taufiq (UNIVERSITY OF LAMPUNG, 2011)
Humic substance (HS) extracted from composted agricultural waste contains organic acids that potential for an acid soil amandement. Functional group of COOH and OH in synthetically organic acid is higher than in HS originated from composted agricultural waste. Addition of synthetically organic acid to the HS may increase its functional group and therefore it will increase effectiveness in detoxifying aluminum (Al) and desorpting phosphorus (P) from an acid soil. Objective of reseach was to determine effect of synthetic organic acid addition to HS extracted from composted organic matter in desorpting P and detoxify Al. Research was conducted at Soil Laboratory of Agricultural Faculty of Jember University from February to May 2010. Treatment consisted of combination of four levels of HS concentration extracted from composted rice straw (0; 1,000; 2,000; and 5,000 mg kg-1) with two kind of synthetic organic acid: ethylenediaminetetraacetic acid (EDTA) and acetic acid (CH3COOH) at concentration of 5 mM. The treatment laid out in a randomized complete by design with three replications. Ultisol collected from Kentrong Banten was used in this reseach. Observation consisted of pH, Al and P concentration in the suspension at 0, 1, 2, 3, and 4 weeks after incubation. The result showed that EDTA or acetic acid treatment at concentration of 5 mM effectively increased soil pH and decreased exchangeable Al (exch-Al). However, EDTA was more reactive and having higher capability in increasing pH and detoxifying exch-Al than acetic acid. Humic substance extracted from composted rice straw at concentration of 1,000 to 5,000 mg kg-1 also effectively increased soil pH, decreased exch-Al, and increased P availability during a 4 week incubation period. The HS effect in Al detoxification and P desorption in acid soil could be boosted by addition of EDTA or acetic acid synthetic